Hubungan Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan CV. Matrix - Elisabeth Pruwo Gebze (Musamus Journal of Business & Management is a peer-reviewed journal published by Faculty of Ecconomics and Business, Musamus University, Merauke Papua Indonesia., 2019)
This study aims to determine whether there is a relationship of work motivation on employee performance in the CV. Matrix Merauke, to find out whether there is a relationship of work discipline to the performance of kariawa on the CV. Merauke Matrix and to find out whether there is a relationship of work motivation and work discipline together on employee performance in the CV. Merauke Matrix. The analysis method used to solve the problem in this study is to use a regression analysis method that is research if all employees of CV. Matrix Merauke as many as 30 people. The results showed that partial motivation had a positive and significant relationship to employee performance. This problem proves that the tcount is greater than the ttable value of 4.948> 1.703 with a significance level of 0.000> 0.05. Thus Ho is rejected and Ha is accepted. Partial work discipline has no positive and significant relationship to employee performance. This problem proves that the value of t value is smaller than the value of ttable which is 0.025 <1.703 with a significance level of 0.839> 0.05. Thus Ho is accepted and Ha is rejected. Simultaneously the variables of work motivation and work discipline have a positive and significant relationship to employee performance. this is evidenced by the calculated F value greater than the Ftable which is 18.866> 3.354 and a significance level of 0.000 <0.005. And thus Ho was refused and Ha was accepted. Keywords: Motivation, Work Discipline, Employee Performance